2018
DOI: 10.1002/cnma.201800302
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Surface‐Bonded MoO2@Carbon Nanocomposites by Nitrogen‐Doping with Outstanding Capability for Fast and Stable Li Storage

Abstract: Strongly surface-bonded MoO 2 @carbon nanocomposites are obtained through in-situ nitrogen-doping of MoO 2 @carbon and evaluated as the anode material of Li-ion batteries. Nitrogen, derived from polydopamine, is in-situ doped into both MoO 2 core and the carbon shell. Strong MoÀN bonding is validated from X-ray photoelectron spectra and Fourier transform infrared spectra. The in-situ nitrogendoping process can generate a strong interfacial interaction between MoO 2 and carbon, facilitating the transport of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The other two peaks at 232.2 and 228.1 eV are attributed to the Mo 3d 3/2 and Mo 3d 5/2 of Mo 4+ in the MoO 2 , respectively [32]. Additionally, the peak at 235.2 eV corresponding to Mo 3d 3/2 of Mo 6+ can be ascribed to the slight oxidation of MoO 2 by calcination in the air atmosphere [33,34]. The Se XPS spectrum (Figure 4c) shows two peaks at 54.4 eV and 53.6 eV, corresponding to Se 2- in MoSe 2 [31].…”
Section: Resultsmentioning
confidence: 99%
“…The other two peaks at 232.2 and 228.1 eV are attributed to the Mo 3d 3/2 and Mo 3d 5/2 of Mo 4+ in the MoO 2 , respectively [32]. Additionally, the peak at 235.2 eV corresponding to Mo 3d 3/2 of Mo 6+ can be ascribed to the slight oxidation of MoO 2 by calcination in the air atmosphere [33,34]. The Se XPS spectrum (Figure 4c) shows two peaks at 54.4 eV and 53.6 eV, corresponding to Se 2- in MoSe 2 [31].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the peaks at 780 cm −1 and 922 cm −1 of Mo–O bond further prove the existence of MoO 2 . 31–34…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the peaks at 780 cm À1 and 922 cm À1 of Mo-O bond further prove the existence of MoO 2 . [31][32][33][34] The morphology of MoO 3 , MoO 3 @PPy and MoO 2 /NC are investigated by SEM measurement. It is obviously observed that the prepared MoO 3 presents 1D nanowires with widths of $300 nm and lengths of several micrometers.…”
Section: Resultsmentioning
confidence: 99%
“…The good electronic conductivity of MoO 2 resulting from the existence of delocalized electrons in its conduction band also facilitates the electronic transport of the ternary MoSe 2 /MoO 2 /NC electrode. 46,[51][52][53] In addition, the porous structure of carbon and ultrasmall nanocrystallite size of MoSe 2 /MoO 2 can facilitate the access of electrolyte to the active material and shorten the diffusion distance of Naions in the electrode bulk. As a result, not only the charge-transfer reactions on the electrode/electrolyte interfaces but also the diffusion of Na-ions in the solid phase will be favourable, which bring about the excellent rate behaviour of MoSe 2 /MoO 2 /NC.…”
Section: àmentioning
confidence: 99%